Safety, Tolerability, Pharmacokinetics, and Antimalarial Activity of the Novel Plasmodium Phosphatidylinositol 4-Kinase Inhibitor MMV390048 in Healthy Volunteers - Sinxadi, Phumla; Donini, Cristina; Johnstone, Hilary; Langdon, Grant; Wiesner, Lubbe; Allen, Elizabeth; Duparc, Stephan; Chalon, Stephan; McCarthy, James S.; Lorch, Ulrike; Chibale, Kelly; Möhrle, Jörg; et al. (Antimicrobial agents and chemotherapy, 2020)
MMV390048 is a novel antimalarial compound that inhibits Plasmodium phosphatidylinositol-4-kinase. The safety, tolerability, pharmacokinetic profile, and antimalarial activity of MMV390048 were determined in healthy volunteers in three separate studies. A first-in-human, double-blind, randomized, placebo-controlled, single-ascending-dose study was performed. Additionally, a volunteer infection study investigated the antimalarial activity of MMV390048 using the Plasmodium falciparum induced blood-stage malaria (IBSM) model. MMV390048 is a novel antimalarial compound that inhibits Plasmodium phosphatidylinositol-4-kinase. The safety, tolerability, pharmacokinetic profile, and antimalarial activity of MMV390048 were determined in healthy volunteers in three separate studies. A first-in-human, double-blind, randomized, placebo-controlled, single-ascending-dose study was performed. Additionally, a volunteer infection study investigated the antimalarial activity of MMV390048 using the Plasmodium falciparum induced blood-stage malaria (IBSM) model. Due to the high pharmacokinetic variability with the powder-in-bottle formulation used in both of these studies, a third study was undertaken to select a tablet formulation of MMV390048 to take forward into future studies. MMV390048 was generally well tolerated when administered as a single oral dose up to 120 mg, with rapid absorption and a long elimination half-life. Twelve adverse events were considered to be potentially related to MMV390048 in the first-in-human study but with no obvious correlation between these and MMV390048 dose or exposure. Although antimalarial activity was evident in the IBSM study, rapid recrudescence occurred in most subjects after treatment with 20 mg MMV390048, a dose expected to be subtherapeutic. Reformulation of MMV390048 into two tablet formulations (tartaric acid and Syloid) resulted in significantly reduced intersubject pharmacokinetic variability. Overall, the results of this study suggest that MMV390048 is well tolerated in humans, and the pharmacokinetic properties of the compound indicate that it has the potential to be used for antimalarial prophylaxis or inclusion in a single-dose cure. MMV390048 is currently being tested in a phase 2a study in Ethiopian adults with acute, uncomplicated falciparum or vivax malaria monoinfection. (The three clinical trials described here were each registered with ClinicalTrials.gov as follows: first-in-human study, registration no. NCT02230579; IBSM study, registration no. NCT02281344; and formulation optimization study, registration no. NCT02554799.)